Efficiency of electrocoagulation method to reduce COD, BOD and TSS in tannery industry wastewater: Application of the box–behnken design - Aguilar Ascón, Edwar (2020)
This study intends to assess the removal efficiency of the chemical oxygen demand (COD), biochemical oxygen demand (BOD), and total suspended solids (TSS) from raw tannery wastewater using electrocoagulation by aluminum electrodes as well as to determine the effects of its main operating factors. Therefore, the response surface methodology was applied through an experimental Box–Behnken design by considering the current intensity (I), treatment time (T), and pH levels as the factors. In addition, the BOD, COD, and TSS removal percentages were considered to be the response variables. The results indicate that the treatment time, current intensity, and pH level were significant for COD and TSS, whereas only the treatment time was significant at a confidence level of p-value < 0.05 for BOD. For COD, the optimal operating conditions were I = 3 A, T = 24 min, and pH = 8.4; for BOD, the optimal operating conditions were I = 3 A, T = 24 min, and pH = 5.5; and for TSS, the optimal operating conditions were I = 2.7 A, T = 19 min, and pH = 7.4. Under these conditions, removal efficiencies of 56.8%, 69.2%, 99.9% were observed for COD, BOD, and TSS, respectively. The results suggest that electrocoagulation is an effective method for removing the parameters under study; therefore, it is a viable alternative for reducing the pollution issues caused by the tannery industry.